La falta de proporcionalidad en la sanción, del daño que causa la violencia intrafamiliar, en la ciudad de Zaruma,durante los años 2010-2011. - Aguilar Sánchez, Karla Gabriela (2014)
In this research, it has defended the hypothesis that it is likely to be established in the Penal Code a specific type that sanctions the product injuries of domestic violence as punishment currently set out in Law 103 is highly flexible and recent times causes for injuries from domestic violence have increased.